Analysis of Islam and Liberalism in Surah An-Nisa Verse 135 and Al-Kahf Verse 29 (Analysis of Maudhu'i's Tafsir Method) - Riyadil Ilmi; Fikri Derus Sumawilaga; Asep Abdul Muhyi (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
Islam has its own view on the issue of liberalism, in this case freedom that is not limited to require or bind people to anything. The meaning of freedom itself in Islam is that everyone is free to express everything but must have its own Islamic value or freedom to religious texts (Al-Qur'an and Hadith). Therefore, this paper will discuss Islam and liberalism, what should be known from the basis of Islam and liberalism, so that we understand the issue itself. The method in this research uses the Descriptive Analysis method, which is research by collecting and presenting data that is in accordance with the truth, then the data is arranged neatly, the data is processed and analysed to provide an explanation related to the problems in the discussion. liberalism at this time has exceeded the limits that exist in Islam, so this understanding is feared to cause doubts in the people in the existing faith of the people.